Carbon dioxide sequestration accompanied by bioenergy generation using a bubbling-type photosynthetic algae microbial fuel cell. (May 2019) - Li, Ming; Zhou, Minghua; Luo, Jianmei; Tan, Chaolin; Tian, Xiaoyu; Su, Pei; Gu, Tingyue
Highlights: B-PAMFC fulfills wastewater treatment, CO2 sequestration and bioenergy production. B-PAMFC performed better than PAMFC in power density and CO2 fixation rate. Algal biofixation combined with solution absorption enhances CO2 sequestration. Urea as nitrogen source promoted the power generation and CO2 sequestration. B-PAMFC is an energy-positive system with a maximum net energy of 1.824 kWh m −3 . Abstract: This study developed a bubbling-type photosynthetic algae microbial fuel cell (B-PAMFC) to treat synthetic wastewater and capture CO2 using Chlorella vulgaris with simultaneous power production. The performance of B-PAMFC in CO2 fixation and bioenergy production was compared with the photosynthetic algae microbial fuel cell (PAMFC) and bubbling photobioreactor. Different nitrogen sources for C. vulgaris growth, namely sodium nitrate, urea, ammonium acetate and acetamide were studied. The maximum CO2 fixation rate in B-PAMFC with 2.8 g L −1 urea reached 605.3 mg L −1  d −1, 3.86-fold higher than that in PAMFC. Urea also enhanced the solution absorption of CO2 . Furthermore, the B-PAMFC reached a high lipid productivity of 105.9 mg L −1  d −1 . An energy balance analysis indicated that B-PAMFC had a maximum net energy of 1.824 kWh m −3, making it a lab-scale energy-positive system. The B-PAMFC with urea as nitrogen source would provide an attractive strategy for simultaneous CO2 sequestration and bioenergy production.